Chitosan-Based Extrafibrillar Demineralization for Dentin Bonding. (February 2019) - Gu, L.S.; Cai, X.; Guo, J.M.; Pashley, D.H.; Breschi, L.; Xu, H.H.K.; Wang, X.Y.; Tay, F.R.; Niu, L.N.
Instability of resin-dentin bonds is the Achilles' heel of adhesive dentistry. To address this problem, a chelate-and-rinse extrafibrillar dentin demineralization strategy has been developed that keeps intrafibrillar minerals within collagen fibrils intact to prevent activation of endogenous proteases that are responsible for collagen degradation within hybrid layers. The objective of the present study was to evaluate the potential of using chitosan >40 kDa as an antimicrobial extrafibrillar dentin-chelating agent to enhance bond durability. Transmission electron microscopy provided evidence for retention of intrafibrillar minerals and smear plugs in dentin conditioned with 1 wt% chitosan. Analyzed by Kruskal-Wallis analysis of variance, Dunn's statistic, and separate Mann-Whitney tests, tensile bond strengths to wet- and dry-bonded dentin indicated that chelating dentin with chitosan for 60 s prior to bonding did not result in a significant decline in resin-dentin bond strength when compared with that of phosphoric acid etching ( P > 0.05). Gelatinolytic activity within the hybrid layers was examined via in situ zymography after 24-h storage or after thermomechanical cycling and analyzed with 3-factor analysis of variance. After 24 h, enzymatic activity was detected only within completely demineralized phosphoric acid–etched dentin, with values derived from dry bonding significantly higher than those derived from wet bonding ( P < 0.05). Negligible fluorescence was detected within hybrid layers when dentin was conditioned with chitosan, even after thermomechanical cycling, as compared with the controls. Reduction in water permeability in chitosan-conditioned dentin, attributed to smear plug retention, also fostered long-term bond stability. Antibacterial testing performed with live/dead staining indicated that the acetic acid–solubilized chitosan possessed antibacterial activities against 3 single-species biofilms: Streptococcus mutans, Actinomyces naeslundii, and Enterococcus faecalis . Taken together, the new chitosan-based extrafibrillar demineralization strategy retains intrafibrillar minerals, reduces endogenous protease-initiated collagen degradation, prevents water permeation within hybrid layers, and kills bacteria on dentin surfaces, which are crucial factors for enhancing resin-dentin bond durability.